1997
DOI: 10.1002/art.1780401020
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging‐determined synovial membrane and joint effusion volumes in rheumatoid arthritis and osteoarthritis. Comparison with the macroscopic and microscopic appearance of the synovium

Abstract: Objective. To evaluate the relationship between synovial membrane and joint effusion volumes determined by magnetic resonance imaging (MRI) and macroscopic and microscopic synovial pathologic findings in patients with rheumatoid arthritis (RA) and osteoarthritis (OA).Methods. Synovial biopsies were performed, and macroscopic grades of synovitis assigned, at preselected knee sites during arthroscopy or arthrotomy in 17 knees with RA and 25 with OA. Synovial inflammation and 9 separate tissue characteristics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(151 citation statements)
references
References 32 publications
5
140
0
5
Order By: Relevance
“…There is growing evidence that MRI is a valid method and can be used as the imaging gold standard against which other measures are compared (1,14). Close correlation between findings with gadolinium-enhanced MRI and histologic findings has been demonstrated in knees (36)(37)(38) and MCP joints (39). Reliability of semiquantitative MRI scores has proven to be good, depending on the design of the study and reader training (9,40).…”
Section: Us Scoring Of Finger Joint Synovitis In Ramentioning
confidence: 99%
“…There is growing evidence that MRI is a valid method and can be used as the imaging gold standard against which other measures are compared (1,14). Close correlation between findings with gadolinium-enhanced MRI and histologic findings has been demonstrated in knees (36)(37)(38) and MCP joints (39). Reliability of semiquantitative MRI scores has proven to be good, depending on the design of the study and reader training (9,40).…”
Section: Us Scoring Of Finger Joint Synovitis In Ramentioning
confidence: 99%
“…In addition, contrast enhancement with gadolinium diethylenetriaminepentaacetic acid (Gd-DTPA) administered intravenously (IV) allows MRI to effectively measure inflammation (4). The technique of dynamic gadolinium-enhanced MRI (DEMRI) provides a quantitative assessment of inflammation based on analysis of changes in the signal intensity (SI) resulting from Gd-DTPA enhancement that are proportional to the Gd-DTPA concentration (7)(8)(9)(10). DEMRI, combined with computer-assisted quantitative analysis, provides a measure of blood perfusion, capillary permeability, and extracellular volume, all of which reflect the inflammatory process of synovitis (11,12).…”
mentioning
confidence: 99%
“…The US analysis reliably detects both abnormalities and it is thus considered an accurate imaging method for the study of synovitis [19,[27][28][29]. Previous studies demonstrated that magnetic resonance analysis of a single sagittal slice and US measurements of synovial thickness in the suprapatellar bursa are reliable and accurate methods for the quantification of the severity of the inflammatory process in RA and in Sj6gren's syndrome patients [19,30,31].…”
Section: Resultsmentioning
confidence: 99%